Optimizing Community Learning Center Operations: A Post-Pandemic Perspective - Siti Nurindah Sari; Masduki Ahmad; Siti Zulaikha (South Sulawesi Education Development (SSED), 2025)
This study explores innovative operational strategies for Community Learning Centers (CLCs) in Indonesia's post-pandemic educational landscape. Using a systematic literature review method, the study analyzed 35 relevant academic and policy sources to investigate how CLCs adapt their organizational frameworks to meet emerging challenges while enhancing operational effectiveness. The findings identify three critical optimization domains: (1) resource mobilization and allocation innovations that combine traditional funding with digital-enabled financial diversification; (2) hybrid service delivery models that strategically integrate physical and virtual learning environments; and (3) adaptive governance structures that enhance organizational resilience. The study emphasizes the importance of context-specific optimization approaches, with urban and rural CLCs facing distinct operational challenges that require tailored strategies. These findings contribute to understanding educational organization management in transitional contexts and provide practical insights for CLC practitioners and policymakers to improve operational sustainability, enhance service accessibility, and ensure long-term institutional adaptability in the evolving educational ecosystem.